What did it mean for Lucas to set up "useful" analogue systems? - Peter Galbács (Duke University, Center for the History of Political Economy (CHOPE), 2020)
This paper provides a look into what Lucas meant by the term 'analogue systems' and how he conceived making them useful. It is argued that any model can be regarded as an analogue system provided it has remarkable predictive success. The term is thus neutral in terms of usefulness. To be useful, Lucas supposed models to meet further requirements. These prerequisites are introduced in two steps in the paper. First, some properties of 'useless' Keynesian macroeconometric models come to the fore as contrasting cases. Second, it is argued that Lucas suggested two assumptions as the keys to usefulness. One is money as a causal instrument, and the other is the choice-theoretic framework to describe the causal mechanisms underlying large-scale fluctuations. It is also argued that Lucas advocated these presumptions for he conceived them to be true. Extensive quotations from Lucas's unpublished materials underpin the claims.
Keywords: 330; Robert E. Lucas; microfoundations; business cycle theory; rational expectations; island models